Komodifikasi Budaya dalam Perayaan Kultural Pasar Malam Tjap Toendjoengan Surabaya dalam Mempertahankan Warisan Kuliner Lokal - Mailarangan, Kardevilla Ferina; Bambang Suharto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tjap Toendjoengan Night Market in Surabaya is a cultural celebration that is not only a major highlight in the city but also a center of cultural, culinary and local economic activities. This research analyzes how the process of cultural commodification occurs in this night market, by considering the transformation of previous culinary practices into products that can be sold and commercialized. The method used is a systematic literature review with the help of the Perish or Publish application and the Google Scholar database using the keywords tjap toendjoengan night market and cultural commodification in 2014 - 2024 and obtained 12 relevant journals and news articles from 100 journals. The findings of this study show that while cultural commodification can provide economic benefits, it is also necessary to be aware of its potential negative impacts, such as a decline in original cultural values or damage to cultural integrity. Therefore, it is important for relevant parties, including night market managers and local governments, to take prudent measures in promoting and maintaining the sustainability of local culture without compromising the integrity of the actual culture. The Tjap Toendjoengan night market can thus serve as a good example for the preservation and sustainable utilization of local cultural heritage.